The Skeletal Cellular and Molecular Underpinning of the Murine Hindlimb Unloading Model - Garg, Priyanka; Strigini, Maura; Peurière, Laura; Vico, Laurence; Iandolo, Donata (Frontiers in Physiology, 2021)
Bone adaptation to spaceflight results in bone loss at weight bearing sites following the absence of the stimulus represented by ground force. The rodent hindlimb unloading model was designed to mimic the loss of mechanical loading experienced by astronauts in spaceflight to better understand the mechanisms causing this disuse-induced bone loss. The model has also been largely adopted to study disuse osteopenia and therefore to test drugs for its treatment. Loss of trabecular and cortical bone is observed in long bones of hindlimbs in tail-suspended rodents. Over the years, osteocytes have been shown to play a key role in sensing mechanical stress/stimulus via the ECM-integrin-cytoskeletal axis and to respond to it by regulating different cytokines such as SOST and RANKL. Colder experimental environments (~20–22°C) below thermoneutral temperatures (~28–32°C) exacerbate bone loss. Hence, it is important to consider the role of environmental temperatures on the experimental outcomes. We provide insights into the cellular and molecular pathways that have been shown to play a role in the hindlimb unloading and recommendations to minimize the effects of conditions that we refer to as confounding factors.